DUKUNGAN SUAMI DENGAN PELAKSANAAN PEMERIKSAAN IVA TEST PADA WANITA USIA SUBUR - Damai Noviasari; Siti Nuryanti; Adminah Adminah (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2021)
Abstract Many women who still do not know and will do the IVA checkpoint because some of the factors that contribute to Support from a husband and provide motivation for early detection screening of cervical cancer. The purpose of the study to know the relationship of husband support with the implementation of the IVA test check on WUS in Sebakung Jaya village. The design on this study a method of diskritif – analitik design with a sectional cross design methods with the preset cross-sectional population in this study is all the WUS that's on Village, Sebakung Jaya, Penajam Paser Utara , samples are taken in random sampling samples by the number of 183 responders. The instruments used were Questionnaire. Research shows there is a significant link between support. The husband with the held IVA test at the WUS with a score of p-0,000 (p< 0.05). This indicates that there is a meaningful sheaf of the support of the husband so that the support of the husband can increase the interest of the WUS in doing the IVA test examination. Keywords : Partner Support , IVA test, reproductive women Abstrak Beberapa wanita yang masih belum mengetahui dan mau melakukan pemeriksaan IVA hal ini dipengaruhi oleh dukungan dari suami dan sebagian besar tingkat pendidikan yang rendah. Tujuan penelitian untuk mengetahui hubungan dukungan suami dengan pelaksanaan pemeriksaan IVA test pada WUS di Desa Sebakung Jaya. Desain pada penelitian ini menggunakan metode diskritif – analitik dengan rancangan cross sectional. Populasi dalam penelitian ini adalah semua WUS yang ada di desa Sebakung Jaya, Penajam Paser Utara. Sampel diambil secara cluster random sampling dengan jumlah sampel 183 responden. Instrumen yang digunakan adalah lembar kuisioner. Hasil penelitian menunjukkan ada hubungan yang signifikan antara dukungan suami dengan pelaksanaan pemeriksaan IVA test pada WUS dengan nilai ρ-0,000 (ρ<0,05). Hal ini menunjukkan bahwa ada hubuangan yang bermakna dari dukungan suami, sehingga dukungan suami dapat meningkatkan minat WUS dalam melaukan pemeriksaan IVA test. Kata kunci : dukungan suami, IVA test, WUS